2014
DOI: 10.1002/cssc.201300793
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Pathways of Hydrohalogenation over Metal‐Free Nitrogen‐Doped Carbon Nanotubes

Abstract: Nitrogen-doped carbon nanotubes (N-CNTs) are found to be active as one novel heterogeneous catalyst for acetylene hydrochlorination reaction, possessing good activity (TOF=2.3×10(-3)  s(-1) ) and high selectivity (>98 %). Compared to toxic and energy-consuming conventional catalysts, such as HgCl2 , N-CNTs are more favorable in terms of sustainability, because of their thermo-stability, metal-free make up, and the wide availability of bulk CNT. Coupling X-ray photoelectron spectroscopy and density functional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 68 publications
(16 reference statements)
6
90
0
1
Order By: Relevance
“…6c indicates that there is a considerable amount of acetylene desorption which covers the temperature range of 50-300°C, higher than the reaction temperature (180°C), validating the capability of NAC1 for activating acetylene directly and in line with the fact that NAC1 exhibits some activity for the hydrochlorination process. DFT study also shows that the nitrogen doping enhanced the formation of the covalent bond between C 2 H 2 and NCNT compared with the undoped CNT, and therefore promoted the addition reaction of the C 2 H 2 and HCl into C 2 H 3 Cl [26][27][28]. After a deposition of 1 wt.% Au onto the AC1 and NAC1 support, a new C 2 H 2 desorption peak appears at 250°C.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…6c indicates that there is a considerable amount of acetylene desorption which covers the temperature range of 50-300°C, higher than the reaction temperature (180°C), validating the capability of NAC1 for activating acetylene directly and in line with the fact that NAC1 exhibits some activity for the hydrochlorination process. DFT study also shows that the nitrogen doping enhanced the formation of the covalent bond between C 2 H 2 and NCNT compared with the undoped CNT, and therefore promoted the addition reaction of the C 2 H 2 and HCl into C 2 H 3 Cl [26][27][28]. After a deposition of 1 wt.% Au onto the AC1 and NAC1 support, a new C 2 H 2 desorption peak appears at 250°C.…”
Section: Resultsmentioning
confidence: 90%
“…Furthermore, the presence of nitrogen atoms in the carbonaceous material tailors their surface properties accordingly, supporting a new idea to employ it as one active substrate for mercury-free hydrochlorination. For example, Bao's group [25,26] and others [27,28] have shown that carbon nitrides can be chemically shaped to a variety of nanostructures, and can catalyze directly transformation of acetylene to vinyl chloride. However, their use on an industrial scale is restricted by the lower activity, and hence limits the production capacity and leads to difficult purification.…”
Section: Introductionmentioning
confidence: 98%
“…The fitting between nitrogen species in N-CNT and reactivity toward hydrohalogenation. Reprinted with permission from [96]. Copyright (2014) Wiley-VCH Verlag.…”
Section: N-cnms As the Catalystsmentioning
confidence: 96%
“…in the oxygen reduction reaction. Thus, in a study of N-CNMs, a possible contribution of metal impurities to the activity should be carefully excluded by additional elucidation of the proper activity of such metals [90,93,95,96] and the presence of metals on the N-CNM surface [90,91] or, in the case of liquid-phase catalysis, by the analysis of solutions for the content of metals [98].…”
Section: N-cnms As the Catalystsmentioning
confidence: 99%
See 1 more Smart Citation